2019
DOI: 10.4038/cjs.v48i3.7648
|View full text |Cite
|
Sign up to set email alerts
|

Chitinases from pitcher fluid of <i>Nepenthes distillatoria</i>

Abstract: Chitinases belong to a diverse family of enzymes among many other hydrolytic enzymes of the pitcher fluid of Nepenthes sp. There are no existing studies on identification of chitinases in Nepenthes distillatoria the only representative of the genus Nepenthes in Sri Lanka. In this study an assay procedure was developed and optimized to detect the chitinolytic activity in the pitcher fluid of N. distillatoria using colloidal Chitin Azure as the substrate. Crude Nepenthes pitcher fluid was subjected to DEAE Cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…β-1,3-Glucosidase, Xylanase, and Carboxylesterase were also determined to be in the pitcher fluid of N. mirabilis [20]. The presence of two or more different chitinases within the pitcher fluid was proven by Senevirathna et al [21]. Another study also reported the prevalence of Putative peroxidase, Class III chitinase, Glucanase, Oxidoreductase, Class IV chitinase, and Acid chitinase from Nepenthes sp.…”
Section: Identified Enzymes In the N Mirabilis Pitcher Fluidmentioning
confidence: 90%
“…β-1,3-Glucosidase, Xylanase, and Carboxylesterase were also determined to be in the pitcher fluid of N. mirabilis [20]. The presence of two or more different chitinases within the pitcher fluid was proven by Senevirathna et al [21]. Another study also reported the prevalence of Putative peroxidase, Class III chitinase, Glucanase, Oxidoreductase, Class IV chitinase, and Acid chitinase from Nepenthes sp.…”
Section: Identified Enzymes In the N Mirabilis Pitcher Fluidmentioning
confidence: 90%